3D printing assisted finite element analysis for optimising the manufacturing parameters of a lumbar fusion cage. (5th February 2019) - Provaggi, Elena; Capelli, Claudio; Rahmani, Benyamin; Burriesci, Gaetano; Kalaskar, Deepak M.
Abstract: The study herein combines the use of fused filament fabrication (FFF) with finite element analysis (FEA) to enhance the understanding of certain manufacturing parameters (i.e. material, infill density, infill pattern, and outer vertical shell) in the design process of a lumbar fusion cage. Three FFF materials with distinct mechanical properties namely polycarbonate (PC), acrylonitrile butadiene styrene (ABS), and polylactic acid (PLA) were tested. Three infill densities (i.e. 25%, 50%, 75%) were investigated along with two different infill patterns (i.e. rectangular and honeycomb). Compressive modulus and compressive yield strength values obtained from standard mechanical analysis were used as input for FEA to assess numerically the mechanical performance of a lumbar fusion cage under physiological static loading. The findings suggest that both infill density and infill pattern influence the quality of the finished part in terms of both printing accuracy and mechanical response. FEA results indicate that both PC and ABS can be safely adopted to fabricate a porous lumbar cage with a 50% honeycomb infill density and a honeycomb infill pattern. This paper demonstrates that 3D printing assisted FEA can be used to predict the performance of a lumbar cage design with varying manufacturing parameters and potentially reduce product design and development time. Graphical abstract: Unlabelled Image Highlights: Porous structures printed by FFF with varying material, infill density, and infill pattern have been studied. Compressive results were used as input for FEA to optimise the manufacturing process of a lumbar fusion cage. Differences in dimensional accuracy, volume fraction, and compressive properties were found between patterns. FEA allowed the selection of optimal materials and cage structure capable to withstand the maximum expected static loads.